Produção de energia elétrica a partir do aproveitamento do bagaço de cana-de-açúcar gerado no setor sucroalcooleiro de Minas Gerais - Bruna de Fátima Pedrosa Guedes Flausinio (2015)
In the age of climate change, Brazil stands out as the holder of more renewable energy mix worldwide (41%), according to the Energy Research Company (Empresa de Pesquisa Energética) in the National Energy Balance (Balanço Energético Nacional BEN) 2014, the base year 2013. Among the sources responsible for renewability of the Brazilian energy matrix is the biomass sugarcane, whose products have taken, from 2007, the lead in domestic energy supply, exceeding the hydraulic energy, which is primarily responsible for electricity generation in the country. However, also already is reality the electricity generation from the burning of sugarcane bagasse in cogeneration plants of this sector. Among the largest national sugarcane producers is the state of Minas Gerais, where the derivatives of sugarcane represent almost 16% of the demand for energy source. Having a representative number of installations, with 39 plants in operation in 2015, the sugar and alcohol sector of Minas Gerais has a potential surplus of electricity production to be sold to the distribution network, able to offer about 15% of electricity from thermal power plants serving the state. Moreover, the generation of electricity from a renewable source contributes to the reduction of greenhouse gas emissions, and represents an energy alternative to hydroelectricity, since the bagasse generation occurs during the harvest of sugar cane during the dry season, when reservoirs decrease the volume of water. This paper quantifies and demonstrates the electricity production capacity from the residual bagasse mass, with reference to the thermoelectric generation technologies used by the industry in the sugar and alcohol sector of Minas Gerais. Evaluating information available in the environmental processes of the plants in operation in Minas Gerais, it was estimated the generation of surplus bagasse around 167.72 t/h. Applying to this total of surplus bagasse the best yields found in cogeneration plants in operation, it is estimated that the sugar and alcohol sector has the potential for sale of electricity around 847 MWh, considering the available energy.